Applications of mindfulness in psychotherapy - Škodlar, Borut (Asian studies, 2016)
Mindfulness has without doubt been the fastest spreading and most popular concept in psychotherapy in the last two decades. Its influence exceeds that of any other individual concept or approach in modern psychotherapy. However, there are many dilemmas, open questions and controversies related to this rapid, almost fanatic spread, which obviously compensates for a certain lack in modern Euro- and Americo-centric societies. Similarly, we are witnessing in the West a lack of reflection, a process of limitless idealization, and the search for a panacea. This all flows with a tint of colonialism, presumptuously taking over ideas, concepts and techniques without a proper study of the primary sources, and with all the accompanying negative side-effects: profiteering, self-promotion, unethical conduct, empty promises of instant rewards, and so on. In the present paper, the development of interest in mindfulness in psychotherapy, as well as the research findings and dilemmas, and concepts and mechanisms of applying mindfulness in psychotherapy, will be reviewed. The main purpose of the paper is to contribute to the critical reflection in studying and applying mindfulness in psychotherapy.
Keywords: čuječnost; psychotherapy research; psihoterapija; psychotherapy; meditacija; meditation